2017
DOI: 10.1177/1748895817720485
|View full text |Cite
|
Sign up to set email alerts
|

The stop and search of minors: A ‘vital police tool’?

Abstract: Police stop and search powers have been widely criticized for the disproportionate manner in which members of black and ethnic minority communities are targeted. However, the use of such powers on minors in England and Wales has largely escaped comment, despite good evidence that such practices are harmful and counterproductive. Whilst data on the stop and search of under-10s and even toddlers has been reasonably widely reported by the mass media, there has been little interest in the welfare of older children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 38 publications
(39 reference statements)
1
23
0
2
Order By: Relevance
“…Young people within ethnic minorities in heavily policed neighborhoods often narrate both individual and collective experiences of police encounters, and they do so in a situated and politically charged way. Previous research suggests that ethnic minority youth are continually singled out by the police, that they are often dissatisfied with the police, and that they understand their dissatisfaction as discrimination (Pettersson 2013(Pettersson , 2014Sollund 2006;Sharp and Atherton 2007;Fassin 2013;Flacks 2017). Police assessments in such contexts are constructed not only on the basis of abstract criteria but also in ways that visualize, draw on and criticize this very context.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Young people within ethnic minorities in heavily policed neighborhoods often narrate both individual and collective experiences of police encounters, and they do so in a situated and politically charged way. Previous research suggests that ethnic minority youth are continually singled out by the police, that they are often dissatisfied with the police, and that they understand their dissatisfaction as discrimination (Pettersson 2013(Pettersson , 2014Sollund 2006;Sharp and Atherton 2007;Fassin 2013;Flacks 2017). Police assessments in such contexts are constructed not only on the basis of abstract criteria but also in ways that visualize, draw on and criticize this very context.…”
Section: Resultsmentioning
confidence: 99%
“…Young ethnic minorities' dissatisfaction with the police, which is often related to discrimination, is a well-explored area (see Fassin [2013] writing about (the city of) Paris, and Goffman [2014] writing about Philadelphia). As far as racial and ethnic profiling is concerned, most research belong to the U.S. and the U.K. (Östlund 2013;c.f.…”
Section: Background and Analytical Frameworkmentioning
confidence: 99%
“…Clayman & Skinns, 2012;Deuchar & Bhopal, 2017;Flacks, 2017;McAra & McVie, 2005;Murray, 2015;Sanders, Young, & Burton, 2010;Weisburd, Wooditch, Weisburd, & Yang, 2016). For instance, McAra and McVie (2005) found that social class such as socio-economic status, neighbourhood and street-life aspects rather than legal issues determines the type of interaction children and young adults have with the police.…”
Section: Perceptions Of Selective Police Stopsmentioning
confidence: 99%
“…Moreover, we argue that the intersections between clothing, ethnicity, hanging out in groups, neighbourhood and ethnicity work to establish our research participants as 'suspicious', 'scary' or 'frightening' in the eyes of the majority population (see also Flacks, 2017), which in turn can expose these young people to future police stops. In particular, the young people sensed that their clothing and looks in general appeared threatening to the police and was the reason for why they were stopped.…”
Section: Perceptions Of Selective Police Stopsmentioning
confidence: 99%
“…Because of this, in the third wave of the ISRD project, a small amount of questionnaire space was devoted to the procedural justice theory (see Box 1). Also taking into account criticism of proactive stop and search policies (or stop-and-frisk in American English) in the United Kingdom (Murray 2014, Scott 2015, StopWatch 2017 and the impact on teenagers (Reid Howie 2002, Flacks 2017, an additional set of questions on stop and search encounters was included in the England and Scotland questionnaire (see Box 2).…”
Section: Introductionmentioning
confidence: 99%